1995
DOI: 10.21273/hortsci.30.2.393
|View full text |Cite
|
Sign up to set email alerts
|

`AU-Sweet Scarlet' Watermelon

Abstract: var has good resistance to race 2 anthracnose, fusarium wilt, and gummy stem blight. 'AU-Sweet Scarlet' originated from the crosses 'Crimson Sweet' x PI 189225, 'All Sweet' x PI 362515, and 'Calhoun Sweet' x 'W.R. Peacock' (Fig. 1). Resistance to gummy stem blight and race 2 anthracnose was incorporated into the breeding lines from plant introductions by a backcross program. Progeny were selected in a screening program with inoculation tests in an incubation chamber and greenhouse as previously described (Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…If this is the case, then this gene may serve as a useful target for engineering of resistance via gene silencing approaches. Recessive GSB resistance controlled by the db gene (Norton 1979) has already been used to breed resistant watermelon cultivars (Norton et al 1986(Norton et al , 1995 and recessive resistance in melon to powdery mildew has also been reported (McCreight 2001). Efforts are underway to set up mapping populations to locate gsb-5 and the other Gsb loci on the genetic map in melon, although a significant impediment to these studies is a relative lack of DNA polymorphism in the species.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, then this gene may serve as a useful target for engineering of resistance via gene silencing approaches. Recessive GSB resistance controlled by the db gene (Norton 1979) has already been used to breed resistant watermelon cultivars (Norton et al 1986(Norton et al , 1995 and recessive resistance in melon to powdery mildew has also been reported (McCreight 2001). Efforts are underway to set up mapping populations to locate gsb-5 and the other Gsb loci on the genetic map in melon, although a significant impediment to these studies is a relative lack of DNA polymorphism in the species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is concern among pathologists and breeders for the development of resistance by S. cucurbitacearum to fungicides (Avenot et al, 2012;Kato et al, 1984;Keinath and Zitter, 1998;Malathrakis and Vakalounakis, 1983;Miller et al, 1997;Thomas et al, 2012;van Steekelenburg, 1987). Resistance to GSB has received attention since the 1970s as a possible alternative to chemical control (Lou et al, 2013;Norton et al, 1986Norton et al, , 1993Norton et al, , 1995.…”
mentioning
confidence: 99%
“…Resistant watermelon cultivars were developed from two crosses ('Jubilee' • PI 271778 and 'Crimson Sweet' • PI 189225) by selecting diseaseresistant seedlings from backcrossed families that had a high yield of excellent quality fruit (Norton et al, 1986). 'AU-Jubilant', 'AU-Producer' (Norton et al, 1986), 'AU-Golden Producer' (Norton et al, 1993), and 'AU-Sweet Scarlet' (Norton et al, 1995) were released, with moderate resistance to GSB. However, they were found less resistant to GSB than the resistant parents PI 189225 and PI 271778.…”
mentioning
confidence: 99%
“…In addition, there is concern among pathologists regarding the development of resistance to fungicides by S. cucurbitacearum (Avenot et al, 2012;Thomas et al, 2012). Resistance to GSB has received attention since the 1970s as a possible alternative to chemical control (Lou et al, 2013;Norton et al, 1986Norton et al, , 1993Norton et al, , 1995.…”
mentioning
confidence: 99%
“…To develop resistant cultivars with a high yield of high-quality fruit, PI 189225 and PI 271778 were chosen as resistant parents in crosses with 'Crimson Sweet' and 'Jubilee'. Several lines with moderate resistance to GSB were released as 'AU-Jubilant', 'AU-Producer' (Norton et al, 1986), 'AU-Golden Producer' (Norton et al, 1993), and 'AU-Sweet Scarlet' (Norton et al, 1995). However, they were much less resistant to GSB than the resistant parents PI 189225 and PI 271778.…”
mentioning
confidence: 99%